Effects of competition and habitat heterogeneity on native‐exotic plant richness relationships across spatial scales. (15th March 2022) - Rossignaud, Laureline; Kimberley, Mark O.; Kelly, Dave; Fei, Songlin; Brockerhoff, Eckehard G.
Abstract: Aim: The biotic resistance hypothesis posits that greater native species richness limits invasions of exotic species. However, negative native‐exotic richness relationships (NERRs) may reverse with increasing spatial scale, seemingly refuting the hypothesis. Here, we explore the effects of species competitive interactions, environmental factors, habitat heterogeneity and vertical vegetation tiers on the NERRs across spatial scales in native forests. Location: New Zealand. Methods: We combined vegetation, land cover and climate data to predict exotic richness from native richness at different vertical tiers (ground to canopy), land cover, plant competition (tree basal area, native ground cover), mean annual temperature and total rainfall. We considered four spatial scales, from single 20 × 20 m plots on an 8‐km grid to groups of plots across grids up to 128 km. Habitat heterogeneity was measured using the variance of climatic conditions among plots within a group. Results: A negative native tree‐exotic richness relationship (NTERR) was observed at plot level but reversed with increasing spatial scale. Species competitive interactions showed a negative relationship with exotic richness at small/intermediate scales (≤32 km). Rainfall and temperature heterogeneity contributed to the positive NTERR at the largest scale. Adjacent exotic grassland cover had a positive relationship with exotic richness across all scales but did not prevent the NTERR from reversing. Main conclusions: Our analysis shows the importance of considering vegetation structure and adjacent land covers, along with spatial heterogeneity and climatic factors, when testing the biotic resistance hypothesis in forest ecosystems. There is a clear indication that biotic resistance is primarily driven by native trees in the overstorey, probably by limiting resources available to ground tier plants. The results support the notion that the NERR is driven by competitive interspecific interactions at small spatial scales and by habitat heterogeneity at larger scales.